Appreciation of peer reviewers for 2014. (7th August 2015) - Becker, Thorsten W.; Bass, Jay; Blichert‐Toft, Janne; Derry, Lou; Lee, Cin‐Ty; Tyburczy, James; Vance, Derek; Yokoyama, Yusuke
Abstract: The editorial and scientific publishing process relies on the sustained work of volunteer reviewers, and evaluating the interdisciplinary and broad interest papers published in G‐Cubed can be a particular challenge. As Editors and Associated Editors, we are therefore hugely appreciative of the efforts of our reviewers, and would like to thank and acknowledge them in this editorial. G‐Cubed published 257 manuscripts out of 431 submissions in 2014, and for this, we were able to rely on the efforts of 710 dedicated reviewers. Their names are listed below; in italics are those 27 who provided three or more reviews. A big thank you from the G‐Cubed team!